Fostering Infrastructure Development Aligned With Sustainable Development Goals - Berawi, Mohammed Ali; Sari, Mustika; Miraj, Perdana (Universitas Indonesia, 2021)
Infrastructure development plays a crucial role in accelerating the sustainable economic growth and development of a country. The increased provision of public infrastructure can help raise the GDP growth level by lowering production costs, enlarging markets, raising total factor productivity,and facilitating economic activities. Furthermore, infrastructure helps improve the living standards of the people by providing jobs and building the local suppliers' and developers’ capabilities, which contribute to reducing poverty and improving development outcomes.On the other hand, infrastructure is also crucial and lies at the core of efforts to achieve sustainable development. It encompasses many aspects of the Sustainable Development Goals (SDGs), such as health, education, access to energy, as well as clean water and sanitation. The infrastructure improvement is implied in most of the targets of SDGs. The importance of infrastructure must take the sustainable development dimension into account; hence greater efficiencies can be obtained to achieve SDGs successfully.Despite its potential benefits, infrastructure development that is poorly planned, implemented, or operated brings negative consequences for the society, which is escalated by an overrun budget and ineffective usage. Therefore, an infrastructure system must be developed to meet sustainability needs. Sustainability in infrastructure can be comprehended as how the attributes of the practices, products, services, and resources used in the infrastructure development can contribute to the continuation of ecosystem components and functions for generations in the future. Infrastructure projects must deliver better value by going hand-in-hand with sustainability, projecting its benefits and costs towards both the short-term goals and long-term implications.In order to be aligned with the dimension of sustainability, infrastructure needs to consider the economic, social, and environmental aspects. In terms of the economic aspect, infrastructure development should contribute to overall growth by supporting inclusivity, boosting productivity, and delivering accessible and affordable services. In terms of the social aspect, infrastructure is supposed to improve livelihoods, enhance human well-being, and remove poverty in all forms. Lastly, in terms of environmental aspects, the development of infrastructure should preserve the natural environment, ecosystems, and the biodiversity within by supporting the use of high-energy efficiency standards and promoting the resource-efficient approach contributing to reducing overall carbon emissions during its lifecycle.As sustainable infrastructure becomes a cornerstone to achieving the SDGs; therefore, the long-term vision for developing a national infrastructure system informed by SDGs should be ensured. We argue that these visions can be delivered by establishing adaptable plans that include implementing low-carbon solutions and resource-efficient, ecologically based, and energy-efficient technologies.